Analisis Fluktuasi Harga Terhadap Faktor-Faktor Yang Mempengaruhi Produktivitas Usaha Tani Cabai Merah di Indonesia - Winda Andini; Siti Kumala Zahra; Muhammad Abdurrahman; Veralianta Br Sebayang (International Forum of Researchers and Lecturers, 2024)
As the years progress in Indonesia, the price and production of chilies tends to fluctuate. This is due to an increase in input costs or production facilities which increase every year, causing price factors for farmers and consumers to tend to change. This literature review analysis aims to determine: (1) factors that significantly influence chili price fluctuations; (2) the influence of production efficiency on the productivity of chili farmers; (3) the influence of marketing channels involved in red chili farming on price fluctuations. The method used is descriptive analysis method with literature study. The results of the literature show that factors that significantly influence price fluctuations are production costs, production facilities, selling price factors, weather factors, use of technology, length of the supply chain where the longer the marketing channel, the higher the price received by final consumers while prices at the farmer level do not experience increase, as well as the availability of red chilies on the market, where if the availability of red chilies is abundant on the market it will cause a decrease in prices at the farmer and consumer level. The results of literature observations show that these three topics are mutually sustainable. So there is an opportunity for further research related to the three subjects for more accurate measurements based on findings in the field.